Karl Polanyi's Political and Economic Thought : a Critical Guide. - Dale, Gareth (Agenda Publishing, 2019)
The work of Karl Polanyi has become a central reference point for scholars in a variety of traditions and disciplines within the social sciences, including international relations, international political economy, economic sociology and economic anthropology. This book offers a comprehensive introduction to Polanyi's political and economic thought by examining the key themes that run throughout it: economic ideas, commodification, money, the gold standard, geopolitical economy, the state, class, fascism, democracy and knowledge. Each chapter introduces the relevant aspects of Polanyi's writings, covering important terminology and the position of the theme in relation to his work more broadly. The contributions seek to engage critically with Polanyi's ideas, analysing both the strengths and weaknesses, as well as highlighting continuing points of relevance to contemporary issues and debates. The book celebrates the diversity of Polanyi's political and economic thought whilst encouraging the reader to see it as a whole and not as a set of fragmented concepts. It is an ideal introduction for students engaging with Polanyi's work for the first time.